Impact load monitoring using inertial measuremement units on different viscoelastic sport surfaces: A technical report - Bradshaw, E. J.; Riice, V.; Landeo, R. (ISBS Proceedings Archive (Michigan), 2018)
Inertial measurement units (IMU) provide the opportunity to measure and monitor loads during gymnastics training on a variety of viscoelastic surfaces. Previously these loads have been estimated from force platform (FP) testing of discrete skills such as somersault landings. This study examined the relationship between peak impact loads measured with an IMU and a FP. A 9 kg slam ball with a fixed IMU was dropped from various heights (40, 60, 80 cm) and surfaces (no mat, rubber, 3-10 cm deep gymnastics mats). There was a significant difference between the two measures for all conditions (p=0.028), except for the 40 cm drop onto the rigid force platform surface. IMUs enable the true load on the gymnast to be measured when completing skills on less rigid, viscoelastic surfaces, which may be lower or higher than what has been previously estimated using force platforms.